The provision of the library service in Perpustakaan Awam Merbok / Mohd lzzuddin Yusof - Yusof, Mohd lzzuddin (2010)
Provision of the library services is needed to searching and using the accurate and precise information. The learning process is now increasingly based on the current environment to find and access knowledge, and to apply it in the daily life. Using the library services that, the users can learn and get the new knowledge based on the services that they used. The provision of the library services is depending on the various factor including attitude, skill, knowledge, promotion and geographical area. The library services are important in the library organization because it will affect the usage of the library users. Perpustakaan A warn Merbok is the rural library under the Perbadanan Perpustakaan A warn Kedah and it is a new library which is starts their operations a few years ago. This study tends to determine the factor that influences the provision of the library services in Perpustakaan A warn Merbok. It will cover on five main factors that can influence the provision of the library services, which attitude, skill, knowledge, promotion and geographical area.